2014
DOI: 10.1038/gt.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for rhesus monkeys heterozygous for LDL receptor deficiency by balloon catheter hepatic delivery of helper-dependent adenoviral vector

Abstract: Autosomal dominant familial hypercholesterolemia (FH) is a monogenic life-threatening disease. We tested the efficacy of low-density lipoprotein receptor (LDLR) gene therapy using helper-dependent adenoviral vector (HDAd) in a nonhuman primate model of FH, comparing intravenous injection versus intrahepatic arterial injection in the presence of balloon catheter-based hepatic venous occlusion. Rhesus monkeys heterozygous for mutant LDLR gene (LDLR+/−) developed hypercholesterolemia while on a high cholesterol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…This approach was successful in decreasing LDL-C levels, but the cholesterol-lowering response during 3-4 months of follow-up was not sustained, and the heterogeneous response to treatment observed showed little promise. 105 …”
Section: Gene Therapymentioning
confidence: 99%
“…This approach was successful in decreasing LDL-C levels, but the cholesterol-lowering response during 3-4 months of follow-up was not sustained, and the heterogeneous response to treatment observed showed little promise. 105 …”
Section: Gene Therapymentioning
confidence: 99%
“…Nevertheless, not all forms of gene therapy tried in the past were efficacious. Next, we will review the scientific evolution of gene therapy for HoFH from the initial approaches using ex vivo transduction with retroviruses in the 1990s 44 and the first clinical trial based in this technology in 1995 45 to the in vivo adenoviral [46][47][48][49][50] and helper-dependent adenoviral (HD-Ad) transduction [51][52][53] and the development of the adeno-associated virus (AAV) vectors [54][55][56][57][58][59][60] that have allowed the current clinical trial in development since 2016 ( figure 3). The limitations of these strategies and their replacement by advanced approaches will also be discussed.…”
Section: Gene Therapy For Hofhmentioning
confidence: 99%
“…52 However, although LDLR overexpression by HD-Ad in rhesus macaques heterozygous for a nonsense mutation in the LDLR gene (LDLR +/-) effectively reversed hypercholesterolaemia, the heterogeneous and unsustained long-term response precludes its future application. 53…”
Section: Hd-ad-mediated Gene Transfermentioning
confidence: 99%
“…The harvested cells were lysed with three freezethaw cycles and incubated in 2 M MgCl 2 and DNase I for 1 h at 37°C. Subsequently, cellular debris were spun down and lysate was subjected to ultracentrifugation, as described elsewhere [14]. Vector concentration was measured as virus particle number determining absorbance at 260 nm.…”
Section: Development Of a Hd-ad Vector For Ldlr-tf Expressionmentioning
confidence: 99%
“…Significant progresses in gene transfer technology have encouraged to develop LDLR gene therapy approaches for FH treatment [9][10][11][12]. In experimental animal models of FH, VLDL receptor overexpression following viral vector-based gene transfer is associated with long-term stable correction of hyperlipidemia, with consequent attenuation of atherosclerosis progression and in certain cases even with lesions regression [13,14]. We also observed that helper-dependent adenoviral (HD-Ad)-mediated human apolipoprotein A-I (hApoA-I) overexpression reduces aortic atherosclerosis development in ApoE-and LDLR-deficient mice [15,16].…”
Section: Introductionmentioning
confidence: 99%